Pengaruh Pendidikan Dan Pelatihan Terhadap Promosi Jabatan Melalui Kinerja (Studi Pada Tenaga Pendidik Di POLTEKAD) - muri2197 -; Ernani Hadiyati; Rini Astuti (Jurnal Ekonomi dan Manajemen, 2020)
Education and training is one of the important factors in the placement of educators in the Army Polytechnic, because the implementation of education and training will make the performance of educators in the Army Polytechnic to be increased or better than before implementing education and training. The results of this study indicate that: i) Education has a significant influence on the performance of educators in the Army Polytechnic; ii) Training has a significant influence on the performance of educators in the Army Polytechnic; iii) Performance has a significant influence on Job promotion for educators in the Army Polytechnic; iv) Education has a significant influence on promotion for educators in the Army Polytechnic; v) Training has a significant influence on promotion for educators in the Army Polytechnic; vi) Education has a significant influence on job promotion through performance for educators in the Army Polytechnic; vii) Training has a significant influence on job promotion through performance for educators at the Army Polytechnic. Keywords: education, training, performance, job promotion